2018
DOI: 10.1155/2018/7814643
|View full text |Cite
|
Sign up to set email alerts
|

Self-Limiting OX513A Aedes aegypti Demonstrate Full Susceptibility to Currently Used Insecticidal Chemistries as Compared to Indian Wild-Type Aedes aegypti

Abstract: OX513A Aedes aegypti is a genetically engineered strain carrying a self-limiting gene. Studies in several countries have shown the effectiveness of the strain at reducing pest Aedes aegypti populations. As a component of biosafety assessments relevant to Indian environments, OX513A and two Indian wild-type Ae. aegypti strains (from Aurangabad and Delhi) were tested for susceptibility to a range of commonly used insecticides in India, such as dichlorodiphenyltrichloroethane (DDT), malathion, deltamethrin, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Short-term laboratory competition studies have been shown to underestimate the fitness costs of the strains analyzed and that a better way to assess the mating competitiveness before field release is through large caged experiments under field conditions [ 20 ]. Our earlier laboratory studies on the mating competitiveness have shown the OX513A strain male adults to be equally competitive against wild type males [ 18 ]. The results of the mating studies under field cages further support that the transgenic OX513A males have similar mating competitiveness, and the AWD females do not preferentially discriminate between the two strains indicating the strain to be competitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term laboratory competition studies have been shown to underestimate the fitness costs of the strains analyzed and that a better way to assess the mating competitiveness before field release is through large caged experiments under field conditions [ 20 ]. Our earlier laboratory studies on the mating competitiveness have shown the OX513A strain male adults to be equally competitive against wild type males [ 18 ]. The results of the mating studies under field cages further support that the transgenic OX513A males have similar mating competitiveness, and the AWD females do not preferentially discriminate between the two strains indicating the strain to be competitive.…”
Section: Discussionmentioning
confidence: 99%
“…This self-limiting approach means that there is no significant persistence of the transgene, and monitoring following field releases of OX513A has documented the complete disappearance of the transgene from the environment [ 14 17 ]. In addition, OX513A mosquitoes have been shown to be susceptible to currently used insecticides [ 18 ]. In 2016, the WHO Vector Control Advisory Group (VCAG) recommended the use of OX513A for pilot deployments in operational contexts in response to the Public Health of International Concern triggered by the Zika pandemic ( http://www.who.int/neglected_diseases/news/mosquito_vector_control_response/en/ ).…”
Section: Introductionmentioning
confidence: 99%
“…Gene drives, which bias inheritance towards a natural or synthetic genetic element or specific allele and lead to a preferential increase of a specific phenotype throughout a population ( Alphey et al., 2020 ), are being developed for mosquito control. Several different gene drives, autonomous/non-autonomous, split, self-limiting drives, etc., have been developed ( Gantz et al., 2015 ; Hammond et al., 2016 ; Patil et al., 2018 ; Adolfi et al., 2020 ; Carballar-Lejarazú et al., 2020 ; Li et al., 2020 ). For instance, a male dominant allele to produce a single sex to reduce tick populations, or a trait to increase refractoriness to pathogens, could be effective strategies for managing tick-borne diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Males and females of all strains showed cent per cent mortality in case of malathion 5%, deltamethrin 0.05% and permethrin 0.75%. In case of DDT 4%, male OX513A showed the highest mortality (90.9%) after 24 hours of application with susceptibility status of "resistance likely" whereas, female OX513A also showed the highest mortality (70.1%) but with susceptibility status of "resistance" category (Patil et al, 2018).…”
Section: A Mosquito Aedes Aegypti Lmentioning
confidence: 96%